A case of eyelid neuroma with recurrent ptosis - Elana Meer; Caitlyn Tse; Raul Del Rosario; Justin Karlin (American Journal of Ophthalmology Case Reports, 2023)
Purpose: We report a rare case of eyelid neuroma, discovered nine years after external levator advancement, presenting with recalcitrant ocular foreign body sensation and pain, persistent corneal epithelial defect, followed by corneal scarring, and ptosis. Observations: An 85-year-old man with a history of multiple skin cancers presented with left ptosis, epiphora and recalcitrant eye pain. Nine years prior to presentation, he underwent excision of melanoma in situ of the left forehead, followed by simultaneous forehead reconstruction and left external ptosis repair. At presentation, he had left ptosis and left superior corneal scarring. Eversion of the eyelid demonstrated the presence of a nodule at the superior border of the tarsus. The patient underwent simultaneous excisional biopsy of the lesion and posterior ptosis repair by Müller muscle conjunctival resection (MMCR). He experienced postoperative resolution of pain, ptosis and epiphora. Histopathologic examination demonstrated the presence of a foreign body granuloma alongside a neuroma. Conclusions: This case highlights the importance of thorough eyelid exam in individuals with ocular surface disease. We review herein the pathophysiology and histopathology of eyelid neuroma.